Dynamics Analysis of Intermittent Transmission Chain System - Huanchun Gong (Jixie chuandong)
The dynamics factors affecting the intermittent motion of the transmission chain system are analyzed. The dynamics modeling method of the transmission chain system is discussed. The dynamics equation of the transmission chain system is established, and then the equation is solved by the modal superposition method. In order to verify the accuracy of modeling, taking the die-cutting machine intermittent transmission chain system as an example，a dynamics experimental device is established to test and analyze the dynamic characteristics of chain intermittent motion. The experimental results show that the modeling method has higher precision. It provides a basis for in-depth study of the characteristics of the intermittent transmission chain system.